Designing and developing for Google Glass thinking differently for a new platform - Firstenberg, Allen; Salas, Jason (O'Reilly Media, 2015)
Creating apps for Google Glass is more involved than simply learning how to navigate its hardware, APIs, and SDK. You also need the right mindset. In three parts--Discover, Design, and Develop--Glass pioneers guide you through the Glass ecosystem and demonstrate what this wearable computer means for users, developers, and society as a whole. You'll learn how to create rich functionality for a consumer technology that's radically different than anything currently available.